Early innate immune responses in European sea bass (Dicentrarchus labrax L.) following Tenacibaculum maritimum infection - Ferreira, Inês A.; Peixoto, Diogo; Losada, Ana Paula; Quiroga, María Isabel; Vale, Ana do; Costas, Benjamín (Frontiers in Immunology, 2023)
Introduction The marine aquaculture industry has been witnessing a worldwide emergence of tenacibaculosis, a poorly understood bacterial disease caused by Tenacibaculum maritimum that affects commercially important fish. So far, knowledge on the T. maritimum virulence mechanisms is scarce and the pathogen-host interaction operating in tenacibaculosis remain to be disclosed. This study aimed at contributing to a better understanding of this disease, by evaluating the early innate immune response triggered in European sea bass (Dicentrarchus labrax) by a bath-challenge with T. maritimum. Methods Groups of sea bass were bath-challenged with T. maritimum (challenged fish) or mock-challenged. Undisturbed fish were used as controls (time 0). Samples of blood, liver and mucosal organs (skin, gills and posterior-intestine) were collected at 0 h (control) and at 6, 24, 48 and 72 h post-challenge (n=12). Mucosal organs were used for analyzing the expression of immune-related genes by RT-qPCR, as well as blood samples for assessing haematological and innate humoral parameters and liver for oxidative stress assessment. Results An increased expression of il-1β, il8, mmp9 and hamp1 was detected in all mucosal organs of infected fish when compared with control and mock-challenged fish, suggesting a pro-inflammatory response against T. maritimum transversal to all organs. The faster induction of these pro-inflammatory genes was observed in the gills. Regarding the systemic response, challenged fish presented neutrophilia, monocytosis, signs of anemia, and a decrease of bactericidal and lysozyme activities in plasma. Almost no variations were observed regarding hepatic oxidative stress. Discussion/Conclusions The present study suggests that T. maritimum induces a local innate immune response upon bath infection not only in the skin of European sea bass, but also in the gills and posterior-intestine, likely triggered by the T. maritimum’s capacity to adhere, colonize and damage these organs that can function as entry ways to bacteria, leading ultimately to the seen host’s systemic response.